FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI MANUFAKTUR DI INDONESIA - Fatma Syara Arzia; Sri Ulfa Sentosa (Universitas Negeri Padang, 2019)
This study aims to determine: (1) the effect of labor on the production of manufacturing industries in Indonesia. (2) the influence of the number of business units on the production of manufacturing industries in Indonesia. (3) the influence of raw materials on the production of manufacturing industries in Indonesia. This study aims to determine and analyze the influence of labor relations, the number of business units and raw materials on the production of manufacturing industries in Indonesia. The data used are panel data from 33 Provinces in Indonesia during the period 2011 to 2015. The type of research used is descriptive and associative. The type of data used is secondary data. This study uses a Random Effect Model (REM) approach. The results of this study indicate that: (1) Labor has a negative and significant effect on the production of manufacturing industries in Indonesia, (2) The number of business units has a negative and significant effect on the production of manufacturing industries in Indonesia, (3) Raw materials have a positive and significant effect on production manufacturing industry in Indonesia.